Smear layer removal for collagen fiber exposure after citric acid conditionings - Cavassim, Rodrigo [UNESP]; Leite, Fábio Renato Manzolli [UNESP]; Zandim-Barcelos, Daniela Leal [UNESP]; Dantas, Andréa Abi Rached [UNESP]; Sampaio, José Eduardo Cezar [UNESP] (My University, 2010)
Aim: The aim of the present study was to compare the removal of the smear layer and exposure of collagen fibers of the root surface following the application of five citric acid solution concentrations. Methods and Materials: Two hundred seventy (270) samples were equally divided into six groups (n=45) for treatment with saline solution (control) and five different concentrations of citric acid (0.5, 1, 2, 15, and 25 percent). Three acid application methods were used (passive, brushing, and burnishing) as well as three application periods (1, 2, and 3 minutes). A previously trained, calibrated (kappa score = 0.93), and blind examiner subsequently scored scanning electron micrographs (SEMs) of the samples. Statistical analyses were performed by using Kruskal-Wallis and Dunn's post-hoc tests. Results: According to the results obtained and within the limitations of the methodology used, the citric acid applications were more effective than the control treatment of applying saline solution (p<0.05). However, no statistically significant differences were observed among the three application methods and three application periods. Descriptive analyses showed that best results for exposure of collagen fibers were obtained with the application of citric acid at 25 percent by brushing for 1 or 3 minutes. Conclusions: The best results for exposure of collagen fibers in this study were obtained with application of citric acid at 25 percent by brushing for 1 or 3 minutes, even though there were no statistically significant differences among the groups. Clinical Significance: The best results for exposure of collagen fibers on root surfaces noted in this study were obtained with application of citric acid at 25 percent by brushing for 1 or 3 minutes. © 2010 Seer Publishing LLC.
Keywords: Acid conditioning collagen fibers; Citric acid; Laboratory study; Root surfaces; Smear layer